The Importance of the Reciprocity Principle for Financial Inclusion - Solarz, Małgorzata (Studia Oeconomica Posnaniensia, 2017)
The article presents the following research hypothesis: reciprocity has a positive impact on the financial resilience of households and thus reduces their susceptibility to financial exclusion. The verification of such a hypothesis was possible as a result of carrying out the main purpose, i.e. determining the importance of the reciprocity principle for establishing financial resilience and the inclusion of households. The analysis is focused on family loans, which constitute the significant source of financing unexpected expenditure to be covered by house-holds and thus an important instrument for creating their financial resilience. Di-agnosing the basic motives followed by people while lending money to relatives allows determining whether, and if so, how important is reciprocity in granting financial support to family members. The following, basic research methods were used in the course of the study: critical analysis of the subject literature, statistical methods and the diagnostic survey method. The empirical data necessary to perform the due analyses originate from two nationwide surveys carried out by the author in Poland in cooperation with the SW Research Agency for Market Research and Opinions in May 2015 and January 2016. The conducted analyses allowed for the positive verification of the presented research hypothesis.